Lobbying Transparency: The Limits of EU Monitory Democracy - William Dinan (Politics and Governance, 2021)
This article examines the origins and current operation of the EU’s lobbying transparency register and offers a critical review of the drivers and politics associated with lobbying reform in Brussels. The analysis considers the dynamics of political communication in EU institutions and draws on concepts of the fourth estate, the public sphere and monitory democracy to illustrate the particular challenges around lobbying transparency and opening up governance processes to wider scrutiny, and wider participation, at the EU level. This article draws upon interviews, official data and participant observation of some of the deliberations on lobbying transparency dating back to the 2005 ETI. The analysis is brought up to date by examining the data within the Transparency Register itself, both substantively in terms of the kinds of information disclosed and in relation to trends around disclosures and registration, since the register was launched over a decade ago. The article concludes with a critical appraisal of the evolving issue culture relating to lobbying transparency in Brussels as well as recommendations for the development of the Transparency Register itself.